The effects of musical auditory stimulation of different intensities on geometric indices of heart rate variability - do Amaral, Joice A. T. [UNESP]; Guida, Heraldo L. [UNESP]; Vanderlei, Franciele M. [UNESP]; Garner, David M.; Osório, Elaine [UNESP]; de Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP] (My University, 2015)
Background Music has been proven to promote changes in cardiac autonomic modulation. However, it is not clear whether the effects of the auditory stimulation on heart rate variability (HRV) are dependent on its intensity. Objective The study intended to investigate the acute effects on the geometric HRV indices of auditory stimulation with heavy metal and baroque music using different intensities of auditory stimulation. Design The study was a nonrandomized, clinical trial. Setting The study was conducted at the facility of the Faculty of Sciences of the São Paulo State University, on the campus in Marilia, Brazil. Participants Participants were 24 healthy women aged between 18 and 27 y. Intervention HRV was recorded for each participant for 10 min at rest. Subsequently, participants were exposed to baroque or heavy metal music through an earphone. They were exposed to 3 equivalent sound levels—60-70 decibels (dB), 70-80 dB, and 80-90 dB—for 5 min in each intensity range. After the first session of baroque or heavy metal music, participants rested for an additional 5 min. Then they were exposed to the other musical style. The first style played for each musical period was randomly selected for all individuals and then the other style would be played automatically for the second session. Outcome Measures The HRV analysis was performed using the following geometrical methods: (1) the triangular index (RRtri), (2) the triangular interpolation of the RR interval histogram (TINN), and (3) the Poincaré plot, using SD1—the standard deviation of the instantaneous variability of the beat-to beat heart rate (HR), SD2—the standard deviation of the long-term, continuous, RR interval variability, and the SD1/SD2 ratio—the ratio between the short- and long-term variations among the RR intervals. Results The classic baroque music by Johann Pachelbel, “Canon in D Major,” did not induce significant changes in the geometric indices of HRV at 60-70 dB, 70-80 dB, or 80-90 dB. However, auditory stimulation with heavy metal music, using “Heavy Metal Universe” by Gamma Ray, decreased the RRtri, TINN, and SD2 at 2 specific sound pressures (60-70 dB and 80-90 dB). Conclusions Auditory stimulation with the selected baroque music did not alter cardiac autonomic modulation, but the selected, heavy metal style of music in the lower and higher intensities reduced the global component of HRV acutely.